A Class of Fourth-Order Telegraph-Diffusion Equations for Image Restoration. (26th June 2011) - Zeng, Weili; Lu, Xiaobo; Tan, Xianghua
Abstract : A class of nonlinear fourth-order telegraph-diffusion equations (TDE) for image restoration are proposed based on fourth-order TDE and bilateral filtering. The proposed model enjoys the benefits of both fourth-order TDE and bilateral filtering, which is not only edge preserving and robust to noise but also avoids the staircase effects. The existence, uniqueness, and stability of the solution for our model are proved. Experiment results show the effectiveness of the proposed model and demonstrate its superiority to the existing models.